Parenting Stress and Quality Of Life Of Special Need Chidren’s Parents: A School Health Survey Among Disabled Children in Badean Bondowoso - Muhammad Cholilurrohman Hadi; Tantut Susanto; Kholid Rosyidi Muhammad Nur (Faculty of Nursing, Universitas Jember, 2019)
The family with special need children experience children’s dependency behavior. This situations related to parenting stress which affected parental quality of life. The objective of this study was to examine the correlation characteristic of parents and parenting stress and parental quality of life among special need children’s parents. A cross sectional study design conducted among 52 parents with special need children in School of Disabled Children in Badean Bondowoso. A self-administered questionnaire including the Alabama Parenting Questionnaire and the World Health Organization Quality of Life-BREF Indonesian version were used to assess parenting stress; and parental quality of life, respectively. Pearson Product Moment and Spearman Rank was performed to answer the objective of this study. The results showed that, there were no correlation between parenting stress and parental quality of life of special need children’s parents (p >0.05). However, length of disability correlated with parenting stress (r = 0.339; p = 0.014). Meanwhile; parent’s gender (Z = -2.089; p = 0.037), special need children’s gender (Z = -2.102; p = 0.036), and number of childrens (r = -0.297; p = 0.033) were correlated with parental quality of life. This study concluded that characteristic of parents and children with special needs correlated with parental quality of life. Therefore, adaptive parenting environment should implement to reduce parenting stress.